Atorvastatin versus Placebo in ICU Patients with COVID-19: Ninety-day Results of the INSPIRATION-S Trial - Talasaz, Azita H.; Sadeghipour, Parham; Bakhshandeh, Hooman; Sharif-Kashani, Babak; Rashidi, Farid; Beigmohammadi, Mohammad Taghi; Moghadam, Keivan Gohari; Rezaian, Somaye; Dabbagh, Ali; Sezavar, Seyed Hashem; Farrokhpour, Mohsen; Abedini, Atefeh; Aliannejad, Rasoul; Riahi, Taghi; Yadollahzadeh, Mahdi; Lookzadeh, Somayeh; Rezaeifar, Parisa; Matin, Samira; Tahamtan, Ouria; Mohammadi, Keyhan; Zoghi, Elnaz; Rahmani, Hamid; Hosseini, Seyed Hossein; Mousavian, Seyed Masoud; Abri, Homa; Sadeghipour, Pardis; Baghizadeh, Elahe; Rafiee, Farnaz; Jamalkhani, Sepehr; Amin, Ahmad; Mohebbi, Bahram; Parhizgar, Seyed Ehsan; Soleimanzadeh, Mahshid; Aghakouchakzadeh, Maryam; Eslami, Vahid; Payandemehr, Pooya; Khalili, Hossein; Talakoob, Hamed; Tojari, Taranom; Shafaghi, Shadi; Tabrizi, Sanaz; Kakavand, Hessam; Kashefizadeh, Alireza; Najafi, Atabak; Jimenez, David; Gupta, Aakriti; Madhavan, Mahesh V.; Sethi, Sanjum S.; Parikh, Sahil A.; Monreal, Manuel; Hadavand, Naser; Hajighasemi, Alireza; Ansarin, Khalil; Maleki, Majid; Sadeghian, Saeed; Barco, Stefano; Siegerink, Bob; Spatz, Erica S.; Piazza, Gregory; Kirtane, Ajay J.; Tassell, Benjamin W. Van; Lip, Gregory Y. H.; Klok, Frederikus A.; Goldhaber, Samuel Z.; Stone, Gregg W.; Krumholz, Harlan M.; Bikdeli, Behnood (Thrombosis and Haemostasis, 2023)
Background In the INSPIRATION-S trial, atorvastatin versus placebo was associated with a nonsignificant 16% reduction in 30-day composite of venous/arterial thrombosis or death in intensive care unit (ICU) patients with COVID-19. Thrombo-inflammatory response in coronavirus disease 2019 (COVID-19) may last beyond the first 30 days.Methods This article reports the effects of atorvastatin 20 mg daily versus placebo on 90-day clinical and functional outcomes from INSPIRATION-S, a double-blind multicenter randomized trial of adult ICU patients with COVID-19. The main outcome for this prespecified study was a composite of adjudicated venous/arterial thrombosis, treatment with extracorporeal membrane oxygenation (ECMO), or all-cause mortality. Functional status was assessed with the Post-COVID-19 Functional Scale.Results In the primary analysis, 587 patients were included (age: 57 [Q1–Q3: 45–68] years; 44% women). By 90-day follow-up, the main outcome occurred in 96 (33.1%) patients assigned to atorvastatin and 113 (38.0%) assigned to placebo (hazard ratio [HR]: 0.80, 95% confidence interval [CI]: 0.60–1.05, p = 0.11). Atorvastatin in patients who presented within 7 days of symptom onset was associated with reduced 90-day hazard for the main outcome (HR: 0.60, 95% CI: 0.42–0.86, pinteraction = 0.02). Atorvastatin use was associated with improved 90-day functional status, although the upper bound CI crossed 1.0 (ORordinal: 0.64, 95% CI: 0.41–1.01, p = 0.05).Conclusion Atorvastatin 20 mg compared with placebo did not significantly reduce the 90-day composite of death, treatment with ECMO, or venous/arterial thrombosis. However, the point estimates do not exclude a potential clinically meaningful treatment effect, especially among patients who presented within 7 days of symptom onset (NCT04486508).
Keywords: statin; atorvastatin; lipid; COVID-19; functional limitations